Coumarin Exhibits Broad-Spectrum Antibiofilm and Antiquorum Sensing Activity against Gram-Negative Bacteria: In Vitro and In Silico Investigation - Qais, Faizan Abul (ACS Omega, 2021)
[Image: see text] Quorum sensing (QS) and biofilm inhibition are recognized as the novel drug targets for the broad-spectrum anti-infective strategy to combat the infections caused by drug-resistant bacterial pathogens. Many compounds from medicinal plants have been found to demonstrate anti-infective activity. However, broad-spectrum anti-QS and antibiofilm efficacy and their mode of action are poorly studied. In this study, the efficacy of coumarin was tested against QS-regulated virulent traits of Gram-negative bacteria. Coumarin inhibited the production of violacein pigment in Chromobacterium violaceum 12472 by 64.21%. Similarly, there was 87.25, 70.05, 76.07, 58.64, 48.94, and 81.20% inhibition of pyocyanin, pyoverdin, and proteolytic activity, lasB elastase activity, swimming motility, and rhamnolipid production, respectively, in Pseudomonas aeruginosa PAO1. All tested virulence factors of Serratia marcescens MTCC 97 were also suppressed by more than 50% at the highest sub-minimum inhibitory concentration. Moreover, the biofilms of bacterial pathogens were also inhibited in a dose-dependent manner. Molecular docking and molecular dynamics (MD) simulation gave insights into the possible mode of action. The binding energy obtained by docking studies ranged from −5.7 to −8.1 kcal mol(–1). Coumarin was found to be docked in the active site of acylhomoserine lactone (AHL) synthases and regulatory proteins of QS. MD simulations further supported the in vitro studies where coumarin formed a stable complex with the tested proteins. The secondary structure of all proteins showed a negligible change in the presence of coumarin. Computational studies showed that the possible mechanisms of anti-QS activity were the inhibition of AHL synthesis, antagonization of QS-regulatory proteins, and blocking of the receptor proteins. The findings of this study clearly highlight the potency of coumarin against the virulence factors of Gram-negative bacterial pathogens that may be developed as an effective inhibitor of QS and biofilms.